Application of Advanced Multi-Sensor Non-Destructive Testing System for the Evaluation of Pavements Affected by Transverse Crack-Heaving. Issue 9 (September 2021) - Zegeye-Teshale, Eyoab; Calhoon, Thomas; Johnson, Eddie; Dai, Shongtao
Pavement tenting, also referred to as crack-heaving, is a distress condition that primarily affects bituminous roads constructed in cold climates. This type of distress spreads over long stretches of roadways and can drastically affect drivers' safety and comfort. The phenomenon occurs in freezing winter temperatures offering a limited and dire time window for testing. This paper discusses using an integrated multi-sensor non-destructive testing methodology to evaluate and characterize pavements affected by tenting. A survey van equipped with high-definition video and thermal cameras, LIDAR laser scanner, high-resolution accelerometer, and ground-penetrating radar (GPR) technologies was used to assess several roads suspected of tenting. The plurality of measuring devices and the data fusion and synchronization capabilities proved useful in revealing important pavement tenting characteristics that would have been otherwise overlooked. The data analysis led to the development of test parameters, derived from longitudinal profile measurements, that captured reasonably well the intensity and frequency of the tented cracks. The parameters were successfully employed to characterize the tested roads and determine the extent of critically affected segments. The study also showed the potential of GPR measurements to investigate underneath moisture conditions contributing to the formation of the tented cracks. Finally, the findings and tools developed in this study were discussed and compared with observations of local engineers who have extensive experience and insight on the subject matter. The knowledge and recommendations gathered in this final effort were also synthesized and incorporated into the paper.